Контроль та ревізія діяльності суб'єктів господарювання в Україні - Сєвідова, І. О.; Sievidova, I. O.; Сусіденко, О. В.; Susidenko, O. V.; Павленко, Н. В.; Pavlenko, N. V.; Олексій Сусіденко; Павленко Наталія Вікторівна; Iryna Sievidova (Економіка та суспільство. - 2024. - Вип. 65, 2024)
Стаття присвячена дослідженню управління та аудиту суб'єктів господарювання в Україні. Автори розглядають основні теоретичні, правові, нормативно-правові, методичні та практичні аспекти управління та аудиту. Основна увага приділена аналізу ефективності застосовуваних методів контролю, проблемам, які виникають підчас проведення аудиту, та запропонованим шляхам їх вирішення. Наукова новизна полягає у визначенні нових підходів до вдосконалення системи управління та аудиту в сучасній економіці України. В умовах сучасної ринкової економіки контроль та ревізія діяльності суб'єктів господарювання є важливими інструментами забезпечення законності та економічної безпеки. В Україні процеси контролю і ревізії стають все більш актуальними з огляду на необхідність підвищення прозорості та відповідальності в діяльності підприємств різних форм власності.

The article is devoted to the study of management and audit of business entities in Ukraine. The authorsconsiders the main theoretical, legal, regulatory, methodological and practical aspects of management and auditing. The main attention is paid to the analysis of the effectiveness of the applied control methods, the problems that arise during the audit, and the proposed ways of solving them. The scientific novelty consists in the definition of new approaches to the improvement of the management and audit system in the modern economy of Ukraine. In the conditions of the modern market economy, control and audit of business entities are important tools for ensuring legality and economic security. In Ukraine, control and audit processes are becoming more and more relevant due to the need to increase transparency and responsibility in the activities of enterprises of various forms of ownership. In modern conditions of the market economy, control and audit of business entities is an integral part of ensuring the stability and efficiency of the state economy. In Ukraine, the control and audit system has undergone significant changes over the past decades, but the existing methods and tools do not always meet the challenges faced by modern business. One of the main problems is insufficient effectiveness of control measures, which is often caused by an outdated methodological base, insufficient qualifications of controllers and auditors, as well as limited available resources. This leads to insufficient quality of financial reporting and a high level of economic offenses, which negatively affects the investment climate and the general economic security of the state. An additional problem is the legislative non-regulation of some aspects of control and audit. Despite the existence of normative acts, such as the Law of Ukraine "On the Basic Principles of State Supervision (Control) in the Field of Economic Activity", there are gaps in the legislation that complicate the process of control and create opportunities for abuse and corruption. The discrepancy between modern challenges and the capabilities of existing control systems requires a rethinking of approaches to control and auditing, the introduction of new methods and technologies, as well as the improvement of the legislative framework. Thus, there is a problem of increasing the efficiency and transparency of control and auditing of business entities in Ukraine, which requires scientific research and the development of specific recommendations for its solution.

Статья посвящена исследованию управления и аудита хозяйствующих субъектов в Украине. Авторы рассматривают основные теоретические, правовые, нормативно-правовые, методические и практические аспекты управления и аудита. Основное внимание уделено анализу эффективности применяемых методов контроля, проблемам, возникающим при проведении аудита, и предложенным путям их решения. Научная новизна состоит в определении новых подходов к усовершенствованию системы управления и аудита в современной экономике Украины. В условиях современной рыночной экономики контроль и ревизия деятельности хозяйствующих субъектов являются важными инструментами обеспечение законности и экономической сохранности. В Украине процессы контроля и ревизии становятся все более актуальными, учитывая необходимость повышения прозрачности и ответственности в деятельности предприятий разных форм собственности.
Control and audit of activities of business entities in Ukraine
Keywords: контроль; ревізія; суб'єкт господарювання; законодавство; методологія; аудит; ефективність; control; audit; business entity; legislation; methodology; audit; efficiency; контроль и ревизия; субъект хозяйствования; законодательство; методология; эффективность